Administration of Progesterone Throughout Pregnancy Increases Maternal Steroids Without Adverse Effect on Mature Oligodendrocyte Immunostaining in the Guinea Pig. (March 2018) - Shaw, Julia C.; Palliser, Hannah K.; Palazzi, Kerrin; Hirst, Jonathan J.
Progesterone is administered to pregnant women at risk of premature labor, despite systematic reviews showing conflicting outcomes regarding its use, highlighting doubt over the effectiveness of the therapy. Progesterone can be rapidly metabolized into a number of steroids, but to date, there has been a lack of investigation into the fetal steroid profiles following administration and whether this impacts fetal neurodevelopment. The objective of this study was to determine the effect of progesterone treatment on allopregnanolone and cortisol levels in the fetus and on a marker of myelination in the fetal brain. We used a guinea pig model where pregnant dams were administered vehicle (β-cyclodextrin) or progesterone orally throughout pregnancy (GA29-61). Maternal and fetal fluids and tissues were collected at both preterm (GA61) and term (GA68) ages. Maternal and fetal progesterone and cortisol were analyzed by enzyme immunoassay and allopregnanolone by radioimmunoassay. Measurement of myelination of fetal brains (hippocampus, cingulum, and subcortical white matter) at preterm and term ages was performed by immunohistochemistry staining for myelin basic protein. We found that dams receiving progesterone had significantly elevated progesterone and cortisol concentrations, but there was no effect on allopregnanolone. Interestingly, the increased cortisol concentrations were not reflected in the fetuses, and there was no effect of progesterone treatment on myelination. Therefore, we conclude that in our guinea pig model, maternal administration of progesterone has no effect on cortisol levels or markers of mature oligodendrocytes in the fetus and suggest this is potentially due to the protective cortisol barrier in the placenta.